Tsunami awareness and preparedness in Aotearoa New Zealand: The evolution of community understanding. (November 2021) - Dhellemmes, Amandine; Leonard, Graham S.; Johnston, David M.; Vinnell, Lauren J.; Becker, Julia S.; Fraser, Stuart A.; Paton, Douglas
Abstract: After catastrophic events such as the 2004 Indian Ocean tsunami and the 2011 Great East Japan earthquake and tsunami there is a clear need for vulnerable countries like Aotearoa New Zealand to get prepared for tsunami. In the last ten years, the New Zealand government initiated major efforts to raise awareness of tsunami risk among coastal residents. This study explores tsunami awareness, preparedness, and evacuation intentions among residents of the East Coast of the North Island in a 2015 survey. The ten chosen locations also participated in a tsunami survey in 2003, with results demonstrating that tsunami awareness rose in the twelve years between the surveys. The 2015 survey also included questions on preparedness and intended action. Even though coastal residents know they live in a tsunami prone area, preparedness is relatively low and high expectations of a formal warning remain, even for a local source tsunami scenario. Furthermore, survey respondents had unrealistic ideas of evacuation procedures. When asked about their evacuation intentions, respondents intended to undertake a number of different actions before evacuating their homes, which could cause significant delays in the evacuation process. Most respondents were also reluctant to evacuate on foot and prefer using their vehicles instead, which could create dangerous traffic congestion. These surveyed intentions are consistent with a study of actual evacuation behaviours in the subsequent 2016 Kaikōura earthquake and tsunami, providing validation for the survey indicators. This paper identifies the procedures least understood by the public and offers some solutions to improve tsunami preparedness. Highlights: A large behaviour intentions survey was conducted in 2015 before the 2016 Kaikōura earthquake and tsunami. An alarming proportion of people were confused as to tsunami arrival time and warning source for a future tsunami. A substantial minority intended to take too long before evacuating, or said they wouldn't evacuate at all. Many people intended to evacuate by car for tsunami that will arrive very soon. Proportions were similar for people's real actions in the 2016 Kaikōura tsunami for two surveyed communities.